Acute transverse myelitis in West Nile Virus, a rare neurological presentation. (2021) - Jani, Chinmay; Walker, Alexander; Al Omari, Omar; Patel, Dipesh; Heffess, Alejandro; Wolpow, Edward; Page, Stephanie; Bourque, Daniel
Highlights: West Nile Virus can lead to various neurological presentation. It is important to identify Acute Transverse Myelitis with the help of imaging. It should be in our differentials in patients presenting with muscular weakness in endemic regions. Abstract: Introduction: West Nile Virus varies in presentation from asymptomatic to a febrile illness often associated with malaise, weakness and maculopapular rash. West Nile neuro-invasive disease often manifests as meningitis, encephalitis, and less commonly acute flaccid paralysis in a "polio-like" presentation. Acute transverse myelitis (ATM) is a rare manifestation. We present a case of neuro-invasive West Nile Virus infection with radiographic evidence of longitudinally extensive transverse myelitis (LETM), a subset of ATM, Case narration: A 42-year-old male from Massachusetts presented with progressive asymmetric paralysis of 4 days duration after developing a prodrome of fever, neck stiffness and urinary retention. Physical examination demonstrated asymmetric lower extremity weakness Lumbar puncture revealed lymphocytic pleocytosis with normal protein and glucose and a positive West Nile IgM in CSF (4.89, reference <0.90), and West Nile Virus detected by PCR in CSF. His West Nile serum IgM was 3.03 (reference range <0.90) and IgG was <1.30 (reference range <1.30). MRI of the lumbar spine showed findings consistent with the diagnosis of ATM. Conclusion: With our patient's presentation of acute onset asymmetrical weakness following a viral illness, we ruled out differentials including demyelinating syndrome such as GBS, inflammation of the meninges through meningitis or meningoencephalitis, or traumatic/ischemic involvement of the spinal cord directly. Due to the MRI findings, his motor weakness and urinary retention, supporting CSF findings and WNV positive serologies, ATM due to WNV infection was the main suspect for his presentation. Although ATM is an uncommon manifestation of WNV, it is imperative to consider this in the differential for patients presenting with acute onset flaccid paralysis in regions where WNV is endemic.